Evaluation Of Branch Achievement Development Of Wrestling, Weightlifting, and Athletic Koni Bengkulu Province - Tono Sugihartono; Santun Sihombing; Anggi Wijaya Kusuma (UNIB Press, 2022)
This study aims to determine the achievement of coaching achievements in the sports of Wrestling, Weightlifting, and Athletics KONI Bengkulu. The type of research used in this research is descriptive qualitative research with a CIPP evaluation research approach. The research subjects were 3 sports, totaling 48 people consisting of 3 coaches, 10 athletes, 3 athletes. Instruments and data collection techniques using observation techniques, questionnaires and documentation. The data analysis technique used is descriptive analysis with percentages. The results of the study are the results of the evaluation of observations both from the monitoring process, the training process, and the condition of the infrastructure. The results of the evaluation stated that the percentage of questionnaires on the achievement development of wrestling, weightlifting and athletics at KONI Bengkulu Province, the average assessment showed the context component was in the